The fourth watcher - Hallinan, Timothy (William Morrow, 2008)
Seeking to retire and settle down with his girlfriend and newly adopted daughter, travel writer Poke Rafferty unexpectedly meets up with his long-lost father, who asks for his help in safeguarding a stolen cache of priceless rubies and forged identity papers.